2014
DOI: 10.2478/s11534-014-0497-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulating genes. Exact steady state solution by using Poisson representation

Abstract: Abstract:Systems biology studies the structure and behavior of complex gene regulatory networks. One of its aims is to develop a quantitative understanding of the modular components that constitute such networks. The self-regulating gene is a type of auto regulatory genetic modules which appears in over 40% of known transcription factors in E. coli. In this work, using the technique of Poisson Representation, we are able to provide exact steady state solutions for this feedback model. By using the methods of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…(iii) The chemical master equation for each model admits an exact solution in steady-state conditions. These exact solutions have been obtained using the method of generating functions but in other studies using similar models, the solution was obtained using the Poisson representation [10,23,24,25]. There are however important differences between the models particularly how they describe protein production and protein-gene interactions that are not often spelled out but can be discerned from the form of the CME.…”
Section: Discrete Models Of Auto-regulationmentioning
confidence: 99%
“…(iii) The chemical master equation for each model admits an exact solution in steady-state conditions. These exact solutions have been obtained using the method of generating functions but in other studies using similar models, the solution was obtained using the Poisson representation [10,23,24,25]. There are however important differences between the models particularly how they describe protein production and protein-gene interactions that are not often spelled out but can be discerned from the form of the CME.…”
Section: Discrete Models Of Auto-regulationmentioning
confidence: 99%
“…Our approach is based on the Poisson representation, initially introduced by Gardiner and Chaturvedi [15] as a powerful ansatz-based technique for solving master equations. As emphasized by the authors, this representation is particularly adapted to chemical birth-death processes because of the particular jump rate form implied by stochastic mass-action kinetics [15,26], and it has already been successfully applied to intracellular kinetics [36] and more specifically to gene expression [20,35,29]. In our case, contrary to the original approach [15] in which all species are included, and as also done tacitly in [20,35], we shall apply the Poisson representation only to the mRNA part (species M) and not to the promoter part (species S i , i ∈ 1, n ).…”
Section: Poisson Representationmentioning
confidence: 99%
“…As emphasized by the authors, this representation is particularly adapted to chemical birth-death processes because of the particular jump rate form implied by stochastic mass-action kinetics [15,26], and it has already been successfully applied to intracellular kinetics [36] and more specifically to gene expression [20,35,29]. In our case, contrary to the original approach [15] in which all species are included, and as also done tacitly in [20,35], we shall apply the Poisson representation only to the mRNA part (species M) and not to the promoter part (species S i , i ∈ 1, n ). The representation then becomes more than just an ansatz by revealing an actual "hidden layer" that turns out to be a piecewise-deterministic Markov process.…”
Section: Poisson Representationmentioning
confidence: 99%
“…The Poisson representation was first introduced by Gardiner and Chaturvedi [11–13] and serves as a powerful tool to investigate the properties of chemical master equations. In particular, it has been used to solve the chemical master equations of some important gene expression models [1416]. Recently, some studies [1719] used the Poisson representation to examine the relationship between discrete and continuous gene expression models and found that the gene product number distributions of some simple discrete and continuous models are related by the Poisson representation.…”
Section: Introductionmentioning
confidence: 99%